(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Good health status is a needed thing to all gender. The power, position, social status, social recognition, respect in family as well as society all determine the efficient health status of an individual. Reproductive health encompasses the full freedom which an individual decides about her own body. If a woman is having the holistic liberty to control her own biological processes, it is being considered as successful reproductive health. But in reality the hands of cultural and religious webs are indirectly controlling the women activities like domestic, social, political as well as their body too. Since the ancient period the woman did not have any rights over their reproductive health. The family system or the male members of the family were acted as the deciding authority over the reproductive health of women. The child marriages, early hood pregnancy, maternal death, passion of having male child were the common things which were affected the health of the women in the past periods. Pregnancy and childbirth are important in the stages of life as they are associated with maternal and infant mortality and morbidity. Culture has a profound influence on beliefs and practices of pregnancy and child care. The present study aims at exploring the beliefs and practices influencing the Reproductive health of Tribal women in India.